1997
DOI: 10.1523/jneurosci.17-18-06974.1997
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of Insulin-Like Growth Factor II in the Songbird Brain

Abstract: Neuronal replacement occurs in the forebrain of juvenile and adult songbirds. To address the molecular processes that govern this replacement, we cloned the zebra finch insulin-like growth factor II (IGF-II) cDNA, a factor known to regulate neuronal development and survival in other systems, and examined its expression pattern by in situ hybridization and immunocytochemistry in juvenile and adult songbird brains. The highest levels of IGF-II mRNA expression occurred in three nuclei of the song system: in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 87 publications
7
43
0
Order By: Relevance
“…Nearly all glutamate receptor subunits/ subtypes showed differential expression in one or more cerebral vocal nuclei. Prior studies have shown differential expression of some genes in songbird and parrot vocal nuclei (Arnold et al, 1976;Bottjer, 1993;Ball, 1994;Casto and Ball, 1994;Aamodt et al, 1995;Holzenberger et al, 1997;Durand et al, 1998;Denisenko-Nehrbass et al, 2000), including the three previously cloned glutamate receptor subunits, NR1, NR2A, and NR2B from songbirds (Singh et al, 2000;Heinrich et al, 2002). However, none have shown systematic differential expression of nearly one entire gene family and across all vocal learning orders.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all glutamate receptor subunits/ subtypes showed differential expression in one or more cerebral vocal nuclei. Prior studies have shown differential expression of some genes in songbird and parrot vocal nuclei (Arnold et al, 1976;Bottjer, 1993;Ball, 1994;Casto and Ball, 1994;Aamodt et al, 1995;Holzenberger et al, 1997;Durand et al, 1998;Denisenko-Nehrbass et al, 2000), including the three previously cloned glutamate receptor subunits, NR1, NR2A, and NR2B from songbirds (Singh et al, 2000;Heinrich et al, 2002). However, none have shown systematic differential expression of nearly one entire gene family and across all vocal learning orders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of HVC by electron microscopy has revealed that the somata of new HVC neurons establish membrane-membrane contacts with mature HVC neurons (Burd and Nottebohm, 1985). Moreover, newly integrated cells often contact multiple mature neurons simultaneously, thereby forming small groups of neurons, which have been referred to as "clusters" (Burd and Nottebohm, 1985;Holzenberger et al, 1997;Kirn et al, 1999). Such cluster organization is evident in the HVC adult zebra finches as well (B.…”
Section: Wandering Migration and The Formation Of Neuronal Clustersmentioning
confidence: 99%
“…Radioactive in situ hybridization of mRNA expression is widely used for multiple purposes, including for studying regional tissue organization, cell types, and brain functional activity [2][3][4][5]10,[12][13][14] . The later use is on genes whose mRNA expression in the brain is dependent on increased neural activity, often called activity-dependent genes or immediate early genes.…”
Section: Discussionmentioning
confidence: 99%
“…With these uses, our method has been applied across multiple species, including in birds, mammals (e.g. human), fish, and amphibians; in multiple tissues, including brain, skin, and muscle; and multiple ages, including hatchlings/neonates, juveniles, adults, and here in whole embryo sections 2,3,5,[15][16][17] . The special features of our protocol include: (1) It produces a balance between anatomical specificity and quantitative specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation